Microtus abbreviatus Miller 1899 - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
130. Insular Vole Microtus abbreviatus French: Campagnol de Saint-Matthew / German: Inselwiihimaus / Spanish: Topillo de San Mateo Other common names: St. Matthew Island Vole Taxonomy. Microtus abbreviatus G. S. Miller, 1899, Hall Island, Bering Sea, Alaska, USA. Two subspecies are recognized. Subspecies and Distribution. M.a.abbreviatusG.S.Miller,1899—knownonlyfromthetypelocalityonHallI,Alaska M. a. fisheri Merriam, 1900 — known only from the type locality on St. M.a. I, Alaska. Descriptive notes. Head-body 111-146 mm, tail 25-32 mm, hindfoot 22-24 mm; weight 45-79 g. An adult Insular Vole has brown dorsum and is pale yellowish laterally and on rump, ear tips, and face. Belly furis lighter bufty color. Habitat. Rocky and willow (Salix, Salicaceae) patches of tundra. On St. Matthew Island, the Insular Vole is most abundant in moist lowlands and on lower slopes. Burrows are in well-vegetated rocky outcroppings. It is not found in dry lowlands or in areas with much standing water. Food and Feeding. Diet is primarily grasses (e.g. Elymus arenarius and Deschampsia caespitosa, both Poaceae), forbs (Rumex arcticus, Polygonaceae and Rhodiola rosea, Crassulaceae), sedges (Carex sp., Cyperaceae), willow, and other herbaceous plants and fungi. Breeding. Insular Voles breed from May until mid-August. Gestation is likely ¢.21 days, and an average of six embryos perlitter have been reported. Young are furred by six days of age, eyes open at eleven days, and weaning occurs at 15 days. Activity patterns. Insular Voles are known to be active during long days of summer. Movements, Home range and Social organization. Population fluctuations of Insular Voles have not been examined because they live in remote areas and are difficult to study. They construct burrows and live in colonies near rocky ridges or along small streams in well-drained soils of lower elevations of Bering Sea Islands. Burrows can be up to 20 cm underground and can include grass-lined nesting chambers. Larger chambers, up to 26-50 cm in size, are used to store ...